Medical Research Trends in Undergraduate Psychological Theses: A report from a South American country - Caycho-Rodríguez, Tomás; Carbajal-León, Carlos; Oré-Kovacs, Nicole; Yupanqui-Lorenzo, Daniel E.; Llerena-Espezúa, Ximena; Becerra Meza, Alvaro Gabriel; Torales, Julio; Díaz Fernandez, Romy (Medicina Clínica y Social, 2023)
Introduction: Psychological research can be conducted by researchers and by undergraduate or postgraduate students. At the undergraduate level, psychological research is especially challenging because of the limited ability of students to develop coherent and logical research problems and methodological approaches. Objective: This study aimed to identify the main research trends in undergraduate psychological theses at Peruvian universities. Quantitative and qualitative research design trends were identified as specific objectives. Methods: A descriptive and retrospective systematic review of psychological research thesis of Peruvian undergraduate students was conducted, starting the data extraction process starting with RENATI database for an initial screening phase. The data analysis was conducted in two phases.  Results: The data were organized according to the following categories: sex of the authors, universities (1–5) according to their ranking, year of publication of the thesis, number of authors, designs, type of methodology, and topic of publication. Descriptive statistics were calculated on the basis of these categories. In the next phase, lexicometric and statistical textual analyses were used to identify research trends. Discussion: The main results showed that different topics were predominantly framed within the clinical and health psychology line of research, mainly those related to coping styles, psychological stress, and well-being.
Keywords: Research; undergraduate; psychological; Peruvian; universities